Getting research into policy - Herpes simplex virus type-2 (HSV-2) treatment and HIV infection: international guidelines formulation and the case of Ghana - Adu-Sarkodie Y; Parkhurst J; Burris H; Mayaud P (BMC, 2011)
Abstract Background Observational epidemiological and biological data indicate clear synergies between Herpes simplex virus type 2 (HSV-2) and HIV, whereby HSV-2 enhances the potential for HIV acquisition or transmission. In 2001, the World Health Organization (WHO) launched a call for research into the possibilities of disrupting this cofactor effect through the use of antiherpetic therapy. A WHO Expert Meeting was convened in 2008 to review the research results. The results of the trials were mostly inconclusive or showed no impact. However, the WHO syndromic management treatment guidelines were modified to include acyclovir as first line therapy to treat genital ulcer disease on the basis of the high prevalence of HSV-2 in most settings, impact and cost-benefit of treatment on ulcer healing and quality of life among patients. Methods This paper examines the process through which the evidence related to HIV-HSV-2 interactions influenced policy at the international level and then the mechanism of international to national policy transfer, with Ghana as a case study. To better understand the context within which national policy change occurs, special attention was paid to the relationships between researchers and policy-makers as integral to the process of getting evidence into policy. Data from this study were then collected through interviews conducted with researchers, program managers and policy-makers working in sexual health/STI at the 2008 WHO Expert Meeting in Montreux, Switzerland, and in Accra, Ghana. Results The major findings of this study indicate that investigations into HSV-2 as a cofactor of HIV generated the political will necessary to reform HSV-2 treatment policy. Playing a pivotal role at both the international level and within the Ghanaian policy context were 'policy networks' formed either formally (WHO) or informally (Ghana) around an issue area. These networks of professionals serve as the primary conduit of information between researchers and policy-makers. Donor influence was cited as the single strongest impetus and impediment to policy change nationally. Conclusions Policy networks may serve as the primary driving force of change in both international context and in the case of Ghana. Communication among researchers and policy-makers is critical for uptake of evidence and opportunities may exist to formalize policy networks and engage donors in a productive and ethical way.